2010
DOI: 10.1182/asheducation-2010.1.153
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Factor VIIa: An Assessment of Evidence Regarding Its Efficacy and Safety in the Off-Label Setting

Abstract: Recombinant human factor VIIa (rFVIIa) is approved by the US Food and Drug Administration for use in the setting of hemorrhage associated with factor VIII or factor IX inhibitors in patients with congenital or acquired hemophilia. This indication represents only a small number of bleeding conditions. Since it became available, rFVIIa has been increasingly used in the management of off-label indications, ranging from emergent hemostasis in traumatic hemorrhage to prophylactic hemostasis in patients undergoing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 49 publications
1
35
0
1
Order By: Relevance
“…The approved dose for inhibitor therapy in hemophilia is 90 g/kg/dose every 2 hours as needed, and for congenital FVII deficiency is 15-30 g/kg/dose every 4-6 hours until hemostasis is obtained. 66 Clinical trials of rFVIIa in the treatment of active bleeding in liver transplantation have used doses ranging from 20-120 g/kg/dose on varying schedules. [67][68][69][70] The clinical efficacy of rFVIIa in the treatment of cirrhotic patients with variceal bleeding has been studied in 2 randomized, doubleblinded trials by Bosch et al, which showed no overall effect of rFVIIa versus placebo and no significant differences in reported mortality, incidence of adverse events, or treatment failure.…”
Section: Rfviia and Prothrombin Complex Concentratesmentioning
confidence: 99%
See 2 more Smart Citations
“…The approved dose for inhibitor therapy in hemophilia is 90 g/kg/dose every 2 hours as needed, and for congenital FVII deficiency is 15-30 g/kg/dose every 4-6 hours until hemostasis is obtained. 66 Clinical trials of rFVIIa in the treatment of active bleeding in liver transplantation have used doses ranging from 20-120 g/kg/dose on varying schedules. [67][68][69][70] The clinical efficacy of rFVIIa in the treatment of cirrhotic patients with variceal bleeding has been studied in 2 randomized, doubleblinded trials by Bosch et al, which showed no overall effect of rFVIIa versus placebo and no significant differences in reported mortality, incidence of adverse events, or treatment failure.…”
Section: Rfviia and Prothrombin Complex Concentratesmentioning
confidence: 99%
“…75 Logan and Goodnough recommended that practicing hematologists exercise restraint in the use of rFVIIa in the off-label setting. 66 aPCCs contain FII, FVII, FIX and FX plus protein C, protein S, and traces of antithrombin, heparin, and vitronectin. These are pooled plasma products that have viral inactivation methods applied during their manufacture.…”
Section: Rfviia and Prothrombin Complex Concentratesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are no large efficacy studies evaluating rFVIIa dosage for off-label administration of rFVIIa in adults, much less children. Consequently, appropriate dosing regimens for off-label usage have not been well established with a wide range described in the literature (2). For example, doses of 5 -160 mcg/kg as a single dose or 45 -400 mcg/kg as a total rFVIIa dose have been reported for management of refractory bleeding following cardiothoracic surgery (4,6).…”
Section: Introductionmentioning
confidence: 99%
“…It functions via two separate mechanisms of action: 1) binding tissue factor (TF) released from subendothelium at sites of vascular injury, with subsequent activation of the common coagulation cascade and generation of activated factor X (FXa), activated factor V (FVa) and thrombin 2) binding activated platelets with surface bound FXa and FVa resulting in thrombin generation. Both mechanisms result in fibrin meshwork formation and clot stabilization at the region of endothelial disruption (1,2).…”
Section: Introductionmentioning
confidence: 99%